THE DIGITAL ENVIRONMENT AND ADOLESCENT PSYCHE: PSYCHOLOGICAL AND BEHAVIORAL CHANGES ARISING FROM THE INFLUENCE OF SOCIAL NETWORKS - Haydarova Dilnoza Bakhtiyorovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  study  investigated  the  impact  of  the  digital  environment, particularly  social  networks,  on  the  adolescent  psyche.  The  study  involved  40 adolescents, analyzing the correlation between their level of social media use and their psychological  state  (depression,  anxiety,  and  behavioral  changes).  The  results indicated  that  excessive  use  of  social  media  is  associated  with  an  increase  in symptoms  of  Depression  and  Anxiety  Disorder.  Furthermore,  cases  of  sleep disturbance,  aggression,  and  social  isolation  were  also  observed  among  the adolescents.